2013
DOI: 10.1016/j.bbagen.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Kineococcus radiotolerans Dps forms a heteronuclear Mn–Fe ferroxidase center that may explain the Mn-dependent protection against oxidative stress

Abstract: The results provide a likely molecular mechanism for the protective role of Mn(II) under oxidative stress conditions as it participates in redox cycling in the hetero-binuclear ferroxidase center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Another example of this type of cofactor replacement is the iron sequestration protein, Dps, in Kineococcus radiotolerans (Figure 2). Dps is a binuclear Fe-containing ferroxidase that binds Fe and precipitates iron oxide inside of the Dps dodecamer; however, the K. radiotolerans enzyme is also active as a mixed metal Mn-Fe enzyme, further evidence for the protective role of Mn(II) via cofactor substitution in the oxidative stress response (Ardini et al, 2013). …”
Section: Manganese As An Antioxidant Micronutrientmentioning
confidence: 99%
“…Another example of this type of cofactor replacement is the iron sequestration protein, Dps, in Kineococcus radiotolerans (Figure 2). Dps is a binuclear Fe-containing ferroxidase that binds Fe and precipitates iron oxide inside of the Dps dodecamer; however, the K. radiotolerans enzyme is also active as a mixed metal Mn-Fe enzyme, further evidence for the protective role of Mn(II) via cofactor substitution in the oxidative stress response (Ardini et al, 2013). …”
Section: Manganese As An Antioxidant Micronutrientmentioning
confidence: 99%
“…SOD activity in S. aureus is significantly diminished in the presence of the host Mn chelator CP and following deletion of the S. aureus Mn importers, mntABC and mntH , supporting the idea that Mn is the Mn‐SOD cofactor in vivo (Kehl‐Fie et al ., , ). Mn is also important for the function of Dps, a protein that protects against hydrogen peroxide via DNA binding, Fe sequestration, and ferroxidase‐activity that reduces H 2 O 2 to H 2 O (Almiron et al ., ; Martinez and Kolter, ; Su et al ., ; Anjem and Imlay, ; Zhao et al ., ; Ardini et al ., ). Mn binds to a regulatory site within Dps to permit DNA‐binding activity and inhibit ferroxidase activity, which serves as a regulatory mechanism that physically separates the two activities such that hydroxide radicals are not produced directly adjacent to DNA (Nguyen and Grove, ).…”
Section: Bacterial Processes That Require Mn During Infectionmentioning
confidence: 97%
“…A distinct, high‐affinity Mn‐binding site is required for ferroxidase activity (Ardini et al ., ); thus, Mn is essential for the full repertoire of Dps function. In addition to its contributions as an enzymatic cofactor, Mn also functions as an antioxidant in a protein‐independent mechanism (Archibald and Fridovich, ; Chang and Kosman, ; Inaoka et al ., ; Tseng et al ., ; Seib et al ., ; Daly et al ., ; Barnese et al ., ; Ardini et al ., ; Culotta and Daly, ; Sharma et al ., ; Tabares and Un, ). This topic has been thoroughly reviewed (Aguirre and Culotta, ; Lisher and Giedroc, ).…”
Section: Bacterial Processes That Require Mn During Infectionmentioning
confidence: 99%
“…It has been previously reported that Mn 2+ can bind to the FOC of Dps (Ardini et al, 2013), which is expected as Fe 2+ and Mn 2+ can assume similar coordination geometries in protein crystal structures (Haikarainen et al, 2011;Zheng et al, 2008). We evaluated the binding of manganese to CjDps by measuring the intrinsic tryptophan fluorescence (Fig.…”
Section: Metal-binding Analysismentioning
confidence: 99%
“…The Streptococcus suis Dps can bind Cu 2+ , Ni 2+ , Co 2+ and Mn 2+ to the FOC, as determined by isothermal titration calorimetry and X-ray crystallography (Haikarainen et al, 2011). Furthermore, Kineococcus radiotolerans Dps can form an Mn-Fe heteronuclear metal cluster at the FOC; however, only iron can be stored inside the protein shell (Ardini et al, 2013). Conserved residues are shaded in black and the arrows indicate the conserved residues at the Dps FOC.…”
Section: Introductionmentioning
confidence: 99%